2022
DOI: 10.1111/cob.12529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre‐surgical aerobic dance‐based exercise on lower extremity in people with morbid obesity awaiting bariatric surgery: Randomized controlled study

Abstract: To investigate what are the effects of pre-surgical aerobic dance-based exercise programme (PSADBE) and physical activity counselling (PAC) programme on lower extremity functions after surgery in people with morbid obesity awaiting bariatric surgery (PMOABS). This study was a single-blind, randomized controlled study.Groups were divided into Group I (PSADBE and PAC) and Group II (PAC). Both groups received PAC, Group I completed the PSADBE programme accompanied by music for 60 min/2 days/8 weeks. Thirty-four P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Answers were obtained in 53% of the cases. 20,21,45,[50][51][52][54][55][56][57][58] Most of the selected studies performed short-term post-surgical evaluations (i.e., between one and 12 months after BS), except for three publications that followed participants up to 2, 56 5, 46 and 9 years 59 post-surgery. Therefore, analyses of the changes in muscle strength/MQ in the medium or long term 60 were not possible as there were insufficient studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Answers were obtained in 53% of the cases. 20,21,45,[50][51][52][54][55][56][57][58] Most of the selected studies performed short-term post-surgical evaluations (i.e., between one and 12 months after BS), except for three publications that followed participants up to 2, 56 5, 46 and 9 years 59 post-surgery. Therefore, analyses of the changes in muscle strength/MQ in the medium or long term 60 were not possible as there were insufficient studies.…”
Section: Resultsmentioning
confidence: 99%
“…67,73 Only one study reported an increase in absolute dynamic strength 12 months after BS in upper and lower limbs. 21 On the other hand, the absolute isokinetic dynamic strength of the lower limbs showed a decrease, 61 no changes, 58 or a 30% reduction after surgery but without reporting a p value. 71 (Table 3).…”
Section: Muscle Strength Outcomesmentioning
confidence: 92%
See 2 more Smart Citations
“…During the assessment sessions, a six-minute walk test, a Stair Climbing Up-Down Test, an Isokinetic Test, PA level measurements, fatigue measurements, and QoL measurements were conducted. Statistically significant improvements were observed in functional capacity, muscle strength and endurance, physical activity (PA), and fatigue scores after treatment and in the fifth month post-surgery in Group I (p < 0.05) [28].…”
Section: Lower Extremity Functionmentioning
confidence: 99%